FT-IR, TG, XRD and SEM Studies of Activated Carbons Prepared From Agricultural Waste - Rajeswara Reddy, B.V.; Chakrapani, Ch.; Suresh Babu, Ch.; Somasekhara Rao, K.; Agarwal, Kavita; Prasad, Mahender (Asian Journal of Chemistry, 2010)
Activated carbon adsorbents were made from Phaseolus trilobus, Leucena leucocephala and Casuarina which are waste bio-mass materials collected from agricultural fields. These raw materials were carbonized under the protection of an inert gas flow with subsequent nitric acid treatment and the resulted carbons surface properties were investigated. X-ray diffraction (XRD) analysis indicated characteristics of graphitic crystallites. Surface chemical groups were detected by absorption bands assigned to carbonyl, phenolic, ethers and surface hydroxyl groups by the Fourier transform infrared spectroscopy (FTIR). Surface morphological studies given by scanning electron microscope (SEM) showed the random arrangement of slant flakes with roughened.